Association of myeloperoxidase levels with cardiometabolic factors and renal function in prepubertal children - Correia-Costa, Liane; Sousa, Teresa; Morato, Manuela; Cosme, Dina; Afonso, Joana; Moura, Cláudia; Mota, Cláudia; Areias, José Carlos; Guerra, António; Schaefer, Franz; Afonso, Alberto Caldas; Barros, Henrique; et al. (European journal of clinical investigation, 2016)
Introduction Myeloperoxidase (MPO), an enzyme linking obesity and cardiovascular (CV) risk in adults, has rarely been studied in young children and no studies assessed its association with renal function. We sought to explore a possible association between serum MPO levels, obesity, CV risk factors and renal function in prepubertal children. Materials/Methods Cross-sectional evaluation of 309 children aged 8-9 years (161 normal weight, 148 overweight/obese), members of the birth cohort Generation I (Portugal). Anthropometrics (body mass index (BMI), waist-to-height ratio (WHtR) and % body fat mass (%BFM) by bioelectrical impedance analysis), 24-h ambulatory blood pressure monitoring and pulse wave velocity (PWV) were measured. Insulin resistance was estimated by the HOMA index (considering serum fasting glucose and insulin determinations). Serum MPO levels were assessed by immunoenzymatic assay. Results MPO levels were positively associated with obesity indices (BMI z-score, WHtR and %BFM). Higher MPO levels were associated with higher 24-h and night-time mean arterial pressure, with nondipping and with higher values of insulin resistance. In normal weight children, the endothelial function, as evaluated indirectly by PWV, was an independent predictor of MPO levels. In overweight/obese children, estimated glomerular filtration rate increased significantly across tertiles of MPO (Ptrend = 0·031) and this association held after adjustment for age, sex, neutrophil and monocyte counts and CV risk factors. Conclusions Our results reinforce the role of MPO as a risk marker in obesity and related CV morbidities in young children. MPO levels associate with the dipping pattern and PWV and, among overweight/obese children, an association exists between MPO and renal function.
First published: 06 November 2015
Gesehen am 05.05.2020